Characteristics of SLS-made 3D gyroid cubic lattice nanoporous polyamide membrane. - Saleh Ahmed Aldahash; Mohammad Kashif Uddin (PLoS ONE)
A novel membrane can enhance the efficiency of various industrial processes and help address critical issues. Membranes made of polyamide are widely used and successful in membrane separation processes. This paper outlines a viable method for creating a three-dimensional gyroid nanostructured polyamide membrane through selective laser sintering. This method has easy setup, fast membrane preparation, no pollution, and low preparation cost. It is better than old-style solvent casting methods, which have inadequate management over the membrane structure. The prepared membrane was characterised using various essential techniques, and its properties were examined. The size of the membrane was 3 × 3 cm. A negative skewness value of -0.107 and a surface roughness of 22.4 nm indicate the presence of small peaks and high roughness. The CHN analysis shows the presence of 8.310% nitrogen, 42.100% carbon, 4.327% hydrogen, and 19.076% sulfur in the prepared membrane. The compressive strength of the membrane was calculated to be approximately 30 Mpa. A preliminary experiment on oil-water separation was conducted to address the growing issue of industrial oily wastewater. This study highlights the critical impact of surface properties on enhancing membrane performance, further solidifying their significance in membrane technology. This study provides insights for optimising membrane performance in future research.